Upregulated expression of PTEN after splenectomy may prevent the progression of liver fibrosis in rats. (15th December 2015) - Li, Nai Shu; Wang, Zi Ming; Lin, Jian Hua
Abstract: Background: The aim of the present study was to investigate the mechanisms of delaying progression of liver fibrosis by splenectomy. Methods: Liver fibrosis was induced by common bile duct ligation. Rats were divided into three groups randomly: group A with common bile duct ligation and splenectomy ( n = 45), group B with common bile duct ligation and spleen sham operation ( n = 45), group C with sham common bile duct ligation and spleen sham operation ( n = 45). Liver samples were collected at the 1st, 3rd and 5th week. H&E staining and Sirius staining were used to evaluate the degree of liver fibrosis, immunohistochemical staining was used to measure the expression of α‐smooth muscle actin (α‐SMA) and PTEN. PTEN mRNA and protein expression was measured by real‐time PCR and Western‐blot. Results: Over time, liver fibrosis developed gradually in groups A and B. The expression of PTEN mRNA and protein in group A was higher than that in group B ( P < 0.05), while the expression of α‐SMA was higher in group B ( P < 0.05). The expression of PTEN was negatively correlated with α‐SMA (r = –0.86, P < 0.05). Conclusions: In this study, splenectomy can upregulate the expression of PTEN and reduce the secretion of α‐SMA, thereby deterring the progression of liver fibrosis. Abstract : Highlight To clarify the effect of spleen removal on liver fibrosis, Lin and colleagues established a liver fibrosis model in rats. Splenectomy was confirmed to up‐regulate the expression of the tumor suppressor gene PTEN and reduce the secretion of a‐SMA in the fibrotic liver, thereby delaying the progression of liver fibrosis.